The power of commitment and the shadow of bureaucracy: factors affecting organisational culture in UK defence equipment and support, 2008-2014 - Shaw, D (2016)
This research exposed some of the factors that affected organisational culture and group behaviour in Defence Equipment and Support (DE&S) from its inception in 2007 through to 2014, when it became a Bespoke Trading Entity. The factors that were examined included organisationally legitimised personal, social and geographic identity, and linguistic difference and group size. Metaphor was also used by group members to describe the relationship they had with their groups. Group size was another factor that affected group behaviour. Finally, the effects of socio-technical induction and socio-cultural integration were seen to be additional factors that allowed cultural drag to occur within DE&S. The research was an insider ethnographic study that used a qualitative, multi-factorial approach which encompassed 6 years of observations, 124 interviews, and included the analysis of appropriate DE&S policy documents. This thesis is considered to be unique because no research of this nature, or at this level, has been carried out in DE&S, the Defence Procurement Agency (DPA) and the Defence Logistics Organisation (DLO). In addition, no studies have investigated the organisational culture of DE&S, apart from Kirke (2007a unpublished), Kirke (2010), which was a published article that was informed by that pilot study. The factors that were identified combined to produce both an organisation that possessed multiple organisational cultures and one single ethos which was that of delivering equipment to troops and supporting the troops, described as ‘front-line-first’. There was also an organisational culture that was affected by both the socio-technical and socio-cultural interactions of its members and of unconscious behaviours. All of those factors acted together as a system of interactions, with different factors taking primacy depending on the organisational context, no single factor being consistently more important than any other. The ethos of “front-line-first” was embedded within the DE&S organisational culture as a value which may have been used as a metaphor for the primacy of the overarching organisational culture of supporting the front-line.